Is internationalisation really an available choice for micro firms producing Cava and Prosecco Superiore? A cross-country, entrepreneurial action perspective - Duarte Alonso, Abel; Kok, Seng (Emerald, 2020)
Purpose – The purpose of this study was to examine pathways towards, and the rationale behind internationalisation from the perspectives of micro firms’ operators involved in the globally competitive wine industry. Moreover, drawing from entrepreneurial action theory, the study developed a theoretical framework to help understanding micro approaches and rationale for internationalisation. Design/methodology/approach – Data were collected through interviews with 19 micro winery owners and managers operating in the Prosecco Superiore (Italy) and Cava industry (Spain). Findings – Aligned with entrepreneurial action theory, uncertainty in participants’ environment, coupled with the associated need to diversify through exports, were predominant drivers of internationalisation. However, internationalisation also emerged through non-deliberate channels, including through growth of wine tourism and increasing foreign wine enthusiasts. Thus, while entrepreneurial action through deliberate means triggered a stronger focus on internationalisation, other passive interventions beyond the control or influence of micro firms, but rather emerge serendipitously, can similarly spur direct action. Originality/value – The study demonstrated its originality and value in various ways, fundamentally, addressing three knowledge gaps, thereby contributing to practical and theoretical discourses with corresponding value, including managerially. First, it extended literature focusing on micro firms, which as compared to small and medium enterprise research is much more limited. Second, it provided a comparative component, which is much rarer in contemporary research discussing internationalisation among micro firms. Third, the study proposed a theoretical framework stemming from the chosen inductive approach, thus, addressing concerns regarding the lack of theoretical rigour or depth in internationalisation activities among micro firms.